The Implementation of Teaching Personal Social Responsibility Through Kasti Ball Games on the Character of Responsibility in Elementary School Students - Mulloh, Farcham; Ma'mun, Amung; Kusmaedi, Nurlan; Abduljabar, Bambang; Hayudi, Hayudi (Papanda Publisher, 2025)
This study investigates the effectiveness of the Teaching Personal and Social Responsibility (TPSR) model, implemented through Kasti Ball, in fostering responsibility among fifth-grade students at SD Negeri Jembangan 2. Using a quasi-experimental design, 30 students were purposively selected and divided into experimental and control groups. The experimental group received four TPSR-integrated kasti ball sessions, while the control group underwent conventional physical education. Responsibility was measured using a validated 20-item Likert-scale questionnaire aligned with Hellison’s five-level responsibility framework. Statistical analysis using paired and independent t-tests showed a significant increase in the experimental group’s responsibility scores (M_pre = 56.20, M_post = 61.80; p < .05), while the control group’s change was not statistically significant (M_pre = 55.47, M_post = 57.80; p = .196). A post-test comparison revealed a significant between-group difference favoring the experimental group (p = .023). Observational data further supported the quantitative findings, showing improved student self-regulation, cooperation, and rule adherence. The study concludes that the TPSR model, when integrated into traditional games like kasti, can effectively promote character development—particularly responsibility—among elementary school students. Teachers and schools are encouraged to adopt culturally relevant, value-based physical education models to reinforce character education holistically.